Numerical analysis of bonded composite patch efficiency in the case of lateral U and V-notched aluminium panels (Fracture and Structural Integrity, 2022)
In this study, the finite element method is applied to investigate the mechanical behavior of aluminium notched structures reinforced by composite patch. In order to evaluate the efficiency of patches in the case of lateral semicircular and V-notches, it is very important to analyze the stress distribution at the notch tip and to take in consideration the influence of the geometrical and mechanical properties of the patch and the adhesive. Simple and double patch were used as reinforcement techniques. Results showed that the stress concentration factor is reduced at the notch tip by using a double patch reinforcement. This reduction becomes more noticeable when the patch thickness increases.
Keywords: Bonded composite patch; Adhesive; Stress concentration factor; Finite element method; notch